MENDORONG KEMAJUAN EKONOMI INDONESIA MELALUI PENGUATAN LITERASI KEUANGAN DIGITAL DAN PENCEGAHAN INVESTASI SCAM: SEBUAH TINJAUAN LITERATUR - Mahirah Marwa Syaharani; Nur Hapijah Sihombing; Khoirun Rizky; Reni Ria Armayani Hasibuan (CV. Barokah Publsiher, 2025)
The growth of the digital economy sector in Indonesia has increased public access to technology-based investment services. However, this development has also led to an increase in investment fraud cases, resulting in significant losses and a decline in public confidence in the investment system. This study uses a literature review method by analyzing various scientific studies that aim to evaluate the role of digital financial literacy in improving investment security and its contribution to national economic growth. The results of the study show that the public’s ability to understand digital financial concepts, recognize security threats, and evaluate investment-related information are important factors in preventing financial fraud. Improving digital financial literacy has also been proven to strengthen consumer protection, increase trust in the digital investment ecosystem, and contribute to accelerating Indonesia’s economic growth.